2015
DOI: 10.1177/107327481502200205
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Assays in Cytopathology for Thyroid Cancer

Abstract: Background Despite lack of adequate, validated, independently performed clinical studies, several molecular tests are commercially available on the market and are being used on indeterminate thyroid nodules to guide patient-care decisions. Methods We summarize the current evidence on the role and limitations of molecular tests used in combination with thyroid cytopathology to refine the presurgical diagnosis of thyroid nodules. Results The clinical performance of molecular tests depends on the pretest risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
1
5
0
2
Order By: Relevance
“…Regulation of miRNAs in thyroid tumors is an extremely complicated process with numerous factors (Valderrabano et al, 2015). We confirmed that miR-27a promotes thyroid cancer migration, invasion, and angiogenesis under both in vitro and in vivo settings.…”
Section: Discussionsupporting
confidence: 68%
“…Regulation of miRNAs in thyroid tumors is an extremely complicated process with numerous factors (Valderrabano et al, 2015). We confirmed that miR-27a promotes thyroid cancer migration, invasion, and angiogenesis under both in vitro and in vivo settings.…”
Section: Discussionsupporting
confidence: 68%
“…45,46 Molecular testing has also been applied effectively in anatomic pathology; an example is in testing equivocal thyroid cytology to better triage patients for surgery. 47,48 An increasing number of these and other new tests demonstrate clinical efficacy and illustrate value for population health. 49 Screening tests are another important area of growth.…”
Section: Precision Medicinementioning
confidence: 99%
“…Тесты AMCs выполняются только на цитологическом материале после проведения ТАБ, содержащем подозрительный или злокачественный цитоморфологический диагноз или подозрительный результат Afirma GEC. AMCs включают изолированный профиль микроРНК для МКЩЖ и/или мутацию гена BRAF V600E для помощи в принятии дальнейшего клинического решения [47].…”
Section: диагностические панели на основе определения мутаций и уровнunclassified